(untitled) (Pesquisa Odontológica Brasileira, 2003)
The aim of this study was to identify the presence of superinfecting microorganisms (Gram-negative enteric rods and Candida sp.) in heart transplant patients and correlate this with gingival overgrowth. Thirty patients (10 females, 20 males - mean age 45 years) were examined. All were under cyclosporin-A (CsA) therapy. Patients who had taken any antibiotics 3 months prior the study or had been submitted to periodontal therapy were not enrolled. Patients were required to have at least 6 teeth. The plaque index (PI), gingival index (GI), pocket depth (PD) and clinical attachment level (CAL) were recorded. Microbiological samples were taken from sulcus/pocket (s/p) and from stimulated saliva (ss) and submitted to analysis. Patients were divided into two groups: the ones with gingival overgrowth (GO) and those without gingival overgrowth (WGO). After statistical analysis (chi-square test, Student's t-test, Fisher test, p < 0.05), we concluded that there was no statistical difference between groups in the parameters of gender, CsA dosage, time since transplantation, PI, GI, PD and CAL. Gram-negative rods from either the sulcus/pocket or saliva samples were not found. Candida sp. was detected (s/p - 30% and ss - 30%). Stimulated saliva samples analysis determined that the presence of Candida sp. was associated with patients without gingival overgrowth.